Impact of the COVID-19 pandemic on the energy performance of residential neighborhoods and their occupancy behavior. (July 2022) - Todeschi, Valeria; Javanroodi, Kavan; Castello, Roberto; Mohajeri, Nahid; Mutani, Guglielmina; Scartezzini, Jean-Louis
Highlights: Exploring Covid-19 impacts on energy performance and user behavior at urban level. A dynamic GIS-based energy model to simulate the hourly energy demand. A machine learning model to improve the accuracy of energy simulations. During the full lockdown residential space heating increased by around 13%. During the full lockdown residential cooling demand increased by around 28%. Abstract: Several contrasting effects are reported in the existing literature concerning the impact assessment of the COVID-19 outbreak on the use of energy in buildings. Following an in-depth literature review, we here propose a GIS-based approach, based on pre-pandemic, partial, and full lockdown scenarios, using a bottom-up engineering model to quantify these impacts. The model has been verified against measured energy data from a total number of 451 buildings in three urban neighborhoods in the Canton of Geneva, Switzerland. The accuracy of the engineering model in predicting the energy demand has been improved by 10%, in terms of the mean absolute percentage error, as a result of adopting a data-driven correction with a random forest algorithm. The obtained results show that the energy demand for space heating and cooling tended to increase by 8% and 17%, respectively, during the partial lockdown, while these numbers rose to 13% and 28% in the case of the full lockdown. The study also reveals that the introduced detailed occupancy scenarios are the key to improving the accuracy of urban building energy models (UBEMs). Finally, it is shown that the proposed GIS-based approach can be used to mitigate the expected impacts of any possible future pandemic in urban neighborhoods. Graphical abstract: Image, graphical abstract